National Community Home Based Care Policy and Guidelines - Malawi Government: Ministry of Health (Malawi Government, 2021)
The HIV/AIDS epidemic has affected all sectors of the economy in Malawi. The health sector has experienced increasing number of patients with HIV/AIDS related infections admitted in hospitals. Most of the patients are chronically ill and although they are discharged in a stable state, they require ongoing care in the home. Care of chronically sick people in the home has existed in the past in different societies. Home care draws on two strengths that exist throughout the world: families and communities. They form the basis of Community home based care v/h \BC i. CHBC provides hope to patients as they receive care in their natural strhngo. maintain independence and achieve the best possible quality of life. T u need for policy and guidelines for CHBC has been urgent; Non vernmental, Community and Faith Based Organization, have been providing CHBC services without any guidelines. This document will assist programme managers, health and social workers in planning, designing, implementation and c luati on of Community Home Based Care services in Malawi. Adherence to the >hcy and guidelines by all implemcniers will ensure improved service delivery, coordination and networking amongst stakeholder institutions at all levels. » r t r ' of Health wishes to appeal to all government agencies, the donor co:nmi..-iity NGOs, FBOs, Civil society and communities to get involved and • • i ate in providing care and support to indiv iduais, families and communities i I ne - ith this policy. Your dedication and commitment is vital in improving the 1 1 ih, -f life for chronically ill patients.